ChemInform Abstract: The Concise Synthesis of Unsymmetric Triarylacetonitriles via Pd‐Catalyzed Sequential Arylation: A New Synthetic Approach to Tri‐ and Tetraarylmethanes. Issue 21 (May 2015) - Nambo, Masakazu; Yar, Muhammad; Smith, Joel D.; Crudden, Cathleen M.
Abstract A series of triarylacetonitriles (VII) is prepared by a sequence of Suzuki—Miyaura cross‐coupling of chloroacetonitrile (I) with boronic acids (II), a C—H arylation of arylacetonitriles (III) with aryl bromides (IV), and a final arylation of diarylacetonitriles (V) with aryl halides (VI).